Pervaporation Dehydration of Ethanol with Malic Acid Crosslinked Graphene/Poly(Vinyl Alcohol) Nanocomposite Membranes - Huu Hieu, Nguyen (Journal of Membrane and Separation Technology, 2016)
Graphene (GE) based poly(vinyl alcohol) (PVA) nanocomposite membranes were prepared by solution blending method. The influence of GE on morphological, structural, and thermal properties of GE/PVA membranes was studied. Then, malic acid (MA) was used as a crosslinker of the nanocomposite membranes. The effect of MA content on the degree of crosslinking, thermal, mechanical properties, and pervaporation (PV) performance of nanocomposite membranes was investigated. The characterizations of GE/PVA and MA crosslinked GE/PVA nanocomposite membranes were performed by X-ray diffraction spectrum, transmission electron microscope, Fourier-transform infrared spectroscopy, and differential scanning calorimetry, and tensile testing. The characterization results indicated that the good compatibility between GE and PVA was obtained with 0.5wt% filler content. Thermal stability and mechanical properties of MA crosslinked GE/PVA membranes were enhanced by adding 20wt% MA with respect to PVA. The best PV performance for dehydration of 50wt% ethanol solution was obtained by using the 20wt% MA crosslinked GE/PVA membrane. This membrane showed that the total permeation flux and selectivity are 0.690kg/m2h and 23.89, respectively.